La gran Pampa Chaqueña - Pautasso, Andrés; Fandiño, Blas; Príncipe, Guillermo; Algarañaz, Natalia; Di Giacomo, Alejandro; Oakley, Luis; Prado, Darién (Revista Aves Argentinas, 2019)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).